Augmented reality-based training to enhance teachers' knowledge of reproductive health for special needs students - Iding Tarsidi; Endang Rochyadi; Budi Susetyo; S. Sunardi; Hendriano Meggy; Dira Rosalia Nurkholifah; Anira Zakiyyah Febrianti; Elvina Hapsari; Naila Cynthia Fajrin (Inovasi Kurikulum, 2024)
Teachers of special schools face significant challenges in delivering reproductive health education to children with special needs because many teachers do not have adequate knowledge and skills in delivering related topics that require delivery adjustments to the mental, physical, and psychological conditions of students. This study aims to measure the effect of augmented reality-based training on improving special school teachers' understanding of how to deal with puberty problems in children with special needs. Using a quantitative approach with a one-group pretest-posttest experimental design, this study involved 30 special education teachers in Bandung City who were selected by purposive sampling. The training provided focused on sexual and reproductive health education and how to deal with puberty problems using AR tools. The data obtained were analyzed using the Wilcoxon Signed-Rank Test, which showed the effectiveness of AR training, as evidenced by increased subject understanding after attending the training. In addition, the varying improvement in subject scores indicates that individual factors influence learning outcomes. These findings suggest that AR-based training is efficacious in improving teachers' understanding of reproductive health and sexuality education for children with disabilities and indicate the need for a more personalized approach in future training. AbstrakGuru Sekolah Luar Biasa (SLB) menghadapi tantangan besar dalam menyampaikan pendidikan kesehatan reproduksi kepada anak berkebutuhan khusus karena banyak guru tidak memiliki pengetahuan dan keterampilan yang memadai dalam menyampaikan topik terkait yang memerlukan penyesuaian penyampaian dengan kondisi mental, fisik, serta psikologis peserta didik. Penelitian ini bertujuan untuk mengukur pengaruh pelatihan berbasis Augmented Reality (AR) terhadap peningkatan pemahaman guru Sekolah Luar Biasa (SLB) dalam menghadapi permasalahan pubertas pada anak berkebutuhan khusus (ABK). Menggunakan pendekatan kuantitatif dengan desain eksperimen one group pretest-posttest, penelitian ini melibatkan 30 guru SLB di Kota Bandung yang dipilih secara purposive sampling. Pelatihan yang diberikan berfokus pada pendidikan kesehatan reproduksi dan seksual serta cara menghadapi permasalahan pubertas dengan menggunakan perangkat AR. Data yang diperoleh dianalisis menggunakan uji Wilcoxon Signed-Rank Test, yang menunjukkan efektivitas pelatihan AR secara signifikan, dibuktikan dengan adanya peningkatan pemahaman subjek setelah mengikuti pelatihan. Selain itu, peningkatan skor subjek yang bervariasi menandakan adanya faktor individu yang memengaruhi hasil belajar. Temuan ini menunjukkan bahwa pelatihan berbasis AR efektif dalam meningkatkan pemahaman guru mengenai pendidikan kesehatan reproduksi dan seksualitas bagi ABK serta mengindikasikan perlunya pendekatan yang lebih personal dalam pelatihan di masa mendatang.Kata Kunci: anak berkebutuhan khusus; augmented reality; pelatihan guru; pendidikan kesehatan reproduksi dan seksual